Relationship between IPSS and Uroflowmetry in Patients with Urinary Symptoms (2019)
Introduction Clinical questionnaires for urinary symptoms were designed to perform an objective evaluation of urinary symptoms and thus avoid invasive and expensive studies. However, patients present symptoms that make difficult the discernment between infravesical obstruction and hypocontractile detrusor. The aim of this study is to determine the correlation between uroflowmetry and symptom severity using the IPSS (International Prostate Symptom Score) in patients with urinary symptoms, compared with urodynamics and to determine its correlation with the diagnosis of infra-vesical obstruction or hypocontractile detrusor. Methods Observational retrospective study in which the clinical records of the patients who consulted for urinary emptying symptoms at La Samaritana University Hospital in Bogotá, Colombia, between April 2016 and April 2017 were reviewed. The IPSS was performed in all patients. Additionally, uroflowmetry and urodynamics were documented with the Medical Measurement System SN077116. Results A total of 27 patients were included in the study. The average age was 67.26 years. The mild IPSS was found in 22% of the patients, moderate 59% and severe 19%. Patterns were identified in uroflowmetry with bell curves in 26% of patients, plateau 41% and intermittent in 33%. 37% of the patients had a Qmax lower than 10 mL/s which was considered obstructive and a PdetQmax less than 40 cm H2O in 37%, which is consistent with the results of uroflowmetry, in addition to being related to high postvoid residual volume. Conclusion There is a correlation between IPSS and Qmax associated with urodynamic patterns. The use of indices as non-invasive methods to reduce costs is comparable with the urodynamic findings; however, there is a non-negligible percentage of patients with Qmax less than 10 mL/s who do not correspond to infravesical obstruction. It is necessary to take into account that up to 23% of patients can have moderate or severe IPSS without the origin of the symptoms being obstructive. © 2019 Sociedad Colombiana de Urología.